“The organizational learning culture and organizational performance in Macedonian companies” - Trpkova nestorovska, Marija; Tevdovski, Dragan; Kekenovski, LJubomir; Cerne, Matej; Dimovski, Vlado; Škerlavaj, Miha (Inderscience Publishers, 2011)
The purpose of the paper is to construct, present and test a model that describes the effect of organisational learning culture on organisational performance improvement. To this end, we use data of 202 Macedonian companies and empirically test the model via structural equation modelling. We found that organisational learning culture has a direct and relatively strong impact on non-financial performance from the employee, customer and supplier perspective. A direct but relatively smaller effect can be noticed on the financial performance. Managers need to be aware that such norms and values that ascribe high importance to information acquisition, distribution and interpretation need to be developed in order to achieve higher levels of organisational performance. The paper contributes to the generalisation of a research model previously tested in more-developed economies based on the data gathered in Macedonia, a developing country in transition.
Keywords: organisational learning culture; competing values framework; organisational performance; structural equation modelling